Wagner or Keynes for Ghana? Government Expenditure and Economic Growth Dynamics. A ‘VAR’ Approach - Kofi Kamasa, Kofi Kamasa; Ofori-Abebrese, Grace (Journal of Reviews on Global Economics, 2015)
This paper analysed empirically the causal relationship between government expenditure growth and GDP growth in Ghana from 1980 - 2010. The study employed vector autoregressive (VAR)/Granger causality analysis developed by Sims (1980) and Granger (1969). The cointegration results provided evidence of a unique cointegrating vector. Granger causality test conducted revealed that causality exist only from GDP growth to government expenditure growth and not the vice versa. This implication supports Wagner’s law of expanding state activities for Ghana. This result means that in estimating government expenditure, GDP growth must be taken into account so as to avoid the problem of misspecification and biasness of estimates generated. The findings also suggest that government must focus on policies that would create the enabling environment for growth to thrive rather than increasing its expenditure with the aim of increasing GDP growth.